2020
DOI: 10.1177/1523422319886288
|View full text |Cite
|
Sign up to set email alerts
|

Globalizing HRD Academic Practice: Developing a Global Mindset for Teaching and Research

Abstract: The Problem As a result of the domination of U.S.- and U.K.-centric approaches to human resource development (HRD), current academic practices often reside in ethnocentric content-related silos, which include certain theoretical frameworks, models, mindsets, and ways of conceptualizing. Given the exponential increase in globalization and the complex global issues facing the field of HRD, these teaching and research practices as well as the limited HRD global and transdisciplinary networks cannot offer the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…First, some scholars are calling for an interrogation of hegemonic methods that dominate HRD research and the inclusion of more culturally responsive methods. One response to this call is the use of indigenous methods (Cseh and Crocco, 2020). Indigenous methods challenge HRD scholars and practitioners to move away from a narrow conceptualization of HRD that resides “within our cultural and scholarly upbringings” and instead incorporates methodological innovations that can “globalize our academic practice and bridge geographical and ideological boundaries” (Cseh and Crocco, 2020, p. 69).…”
Section: Pushing the Needle Even Furthermentioning
confidence: 99%
See 1 more Smart Citation
“…First, some scholars are calling for an interrogation of hegemonic methods that dominate HRD research and the inclusion of more culturally responsive methods. One response to this call is the use of indigenous methods (Cseh and Crocco, 2020). Indigenous methods challenge HRD scholars and practitioners to move away from a narrow conceptualization of HRD that resides “within our cultural and scholarly upbringings” and instead incorporates methodological innovations that can “globalize our academic practice and bridge geographical and ideological boundaries” (Cseh and Crocco, 2020, p. 69).…”
Section: Pushing the Needle Even Furthermentioning
confidence: 99%
“…One response to this call is the use of indigenous methods (Cseh and Crocco, 2020). Indigenous methods challenge HRD scholars and practitioners to move away from a narrow conceptualization of HRD that resides “within our cultural and scholarly upbringings” and instead incorporates methodological innovations that can “globalize our academic practice and bridge geographical and ideological boundaries” (Cseh and Crocco, 2020, p. 69). This innovative thinking within HRD can, for example, include evaluation studies using Talking Circles (Brown and Di Lallo, 2020), or the application of the four types of indigenous research in methods decisions as synthesized by Chai et al (2016).…”
Section: Pushing the Needle Even Furthermentioning
confidence: 99%
“…Although indigenous research in HRD has been minimal and conducted under different topics and foci, HRD scholars are on the road to this under-researched area: McLean (2017) continued his international research agenda by emphasizing the importance of culture, indigenous research, and cross-cultural research to move beyond Western-centric HRD research through the development of indigenous instruments and the use of a broad range of methodologies, including action research. Witnessing the current ethnocentric content-related silos in HRD, Cseh and Crocco (2020) suggested developing students with a global mindset in line with sustainability, diversity, and inclusion through an understanding of indigenous approaches to learning and working, including grounded theory approaches and collaboration with scholars from other countries to develop new indigenous HRD theories. To include more culturally responsive methods in HRD research, Grenier et al (2022) suggested using indigenous methods, such as Talking Circles (Brown & Di Lallo, 2020) that are safe places where relationships are built and Two-Eyed Seeing (Wright et al, 2019) that embraces both Western and indigenous worldviews in indigenous research.…”
Section: Taking Stock Of the Literature On Indigenous Research In Hrd...mentioning
confidence: 99%
“…Although Tsui (2004), refers to the need “to derive new theories of the phenomena in their specific context” (p. 501) to ensure high quality indigenous research, and (Wang, 2012) recommend grounded theory building, ethnography, and phenomenological research in HRD indigenous research, after almost two decades there is still a dearth of indigenous HRD research. This phenomenon could be explained by the hegemony of US-based, UK-based, and European-based HRD theories, frameworks, models, and literature (Cseh & Crocco, 2020) in informing the conceptualization of HRD indigenous research conducted by international doctoral students and/or alumni.…”
Section: Questioning the Meaning Behind The English Language Concepts...mentioning
confidence: 99%
“…Yet in doing so, the facts that people are complex and the world in a pandemic is far from predictable are ignored. In avoiding the messiness, organizations likely only share that which is easy to capture, translate, reproduce, and package, leaving HRD scholarship limited to “ethnocentric content-related silos” (Cseh & Crocco, 2020, p. 57). Without including a diversity of critically reflexive method/ologies, researchers cannot fully grasp the complexities of human experience.…”
mentioning
confidence: 99%